An Investigation into the Effect of Self-assessment on Improving EFL Learners' Motivation in EFL Grammar Achievements - Vahid Norouzi Larsari; Raju Dhuli; Zahra Darvishi Koolai (Journal of English as A Foreign Language Teaching and Research, 2023)
In recent years, there has been an increasing focus on the role of the student in the learning process and boosting motivation for English as Foreign Language (EFL) learners. Motivation is widely considered to be a key aspect of being a successful learner. Moreover, there is a general consensus in the literature that motivation is one of the key learner characteristics. This present study aims to examine the impact of self-assessment as an alternative form of assessment on enhancing motivation and EFL learners' grammar achievements. To this end, the students in the experimental and control groups were all exposed to the same content and instructional method and had the same instructor. There was only one difference. The students in the experimental group self-assessed themselves, while the students in the control group were assessed by their instructor. The design of methodology is quasi-experimental design. The results revealed that self-assessment has a strong role in promoting the learners' motivation in EFL grammar achievements. The results have provided further evidence confirming that self-assessment as an alternative form of assessment is a useful for accounting for students' performance and learning. The present study has shed light on how self-assessment was found to affect learners' achievements and motivation in class. The issue of English grammar instruction in EFL classroom is intriguing and could have some recommendations for future research. As discussed in methodology, the method applied for control group was the conventional method, while a further study could present teaching grammar through other methods.